Silicon nano wires solar cell - Mohamed, Sara (AUC Knowledge Fountain, 2014)
Improving the optical absorption capability of solar cells' materials is a crucial factor in increasing their power conversion efficiency. To this end, the absorption can be enhanced by minimizing the reflection and the transmission out from the absorbing layer. While the reflection can be minimized using an antireflection coating, the transmission can be minimized by exploiting a light- trapping mechanism. In this thesis, the Si nanowires have been utilized to enhance the absorption and photocurrent without the need for antireflection coating, and provide high field localization, which in turn enhances the overall efficiency of the solar cell. Vertically orientated single crystalline silicon nanowire (SiNW) arrays with controlled diameters have been fabricated via a metal-assisted chemical etching (MACE) method. The diameter of the fabricated nanowires is controlled by simply varying the etching time in HF/H2O2 solution. The fabricated SiNWs have diameters ranging from 117 to 650 nm and length from 8 to 18 ÃŽÂ¼m. The optical measurements show a significant difference in the reflectance/absorption of the SiNWs with different diameters, where the reflectance increases with increasing the diameter of the SiNWs. The optical absorption also has been measured at different incident light angle to determine the best angle for absorption. The best absorption angle for different diameters was 10o.The SiNWs showed significant photoluminescence (PL) emission spectra with peaks lying between 380 and 670 nm. The PL intensity increases as the diameter increases and shows red shift for peaks at ~ 670 nm. The increase or decrease of reflectivity is coincident with PL intensity at wavelength ~ 660 nm. The x-ray diffraction (XRD) patterns and high-resolution transmission electron microscope (HR-TEM) confirm the high crystallinity of the fabricated SiNWs. In addition, the Raman spectra showed a shift in the first order transverse (1TO) band toward lower frequencies compared to that usually seen for c-Si. The current-voltage characteristics have also been investigated using photoelectrochemical cell. The measurements have been done in two electrolytes; 10% HF 10% and hydrobromic acid (40%) and bromine (3%). The measurements have been done for the fabricated Si nanowires with different diameters under dark and illumination conditions. The resulted photocurrent decreases with increasing the diameter of SiNWs, which has been explained based on the Debye length of SiNWs. Full wave electromagnetic analysis has been performed using finite difference time domain simulations (FDTD) to confirm the effect of change of diameter on the optical properties of the nanowires. The simulation results show good agreement with the experimental findings for the SiNWs of different diameters. Also, the simulation has been done for different incident light angles to investigate the best incident angle that results in the highest absorption and minimum reflection.